2005
DOI: 10.1001/archpsyc.62.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Residence and Mental Health Problems of 5- to 11-Year-Olds

Abstract: A large number of children in poor neighborhoods have mental health problems. The mechanism through which neighborhood economic effects operated was community social control and cohesion, which may be amenable to intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
358
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(390 citation statements)
references
References 56 publications
26
358
4
2
Order By: Relevance
“…Although population research has established robust effects of poverty and inequality on these outcomes (37)(38)(39)(40)(41)(42), neural mechanisms of these effects have not been a primary focus in population approaches. However, within neuroscience and health psychology, research has begun to show that early life experiences such as parenting and SES have effects on brain areas such as the amygdala and prefrontal cortex (43)(44)(45)(46)(47), areas that have also been linked to a variety of relevant outcomes such as crime and violence (48,49), depression (50), social cognition (51,52), drug use (53,54), and cognitive control (55).…”
Section: Current Practices In Neuroimagingmentioning
confidence: 99%
“…Although population research has established robust effects of poverty and inequality on these outcomes (37)(38)(39)(40)(41)(42), neural mechanisms of these effects have not been a primary focus in population approaches. However, within neuroscience and health psychology, research has begun to show that early life experiences such as parenting and SES have effects on brain areas such as the amygdala and prefrontal cortex (43)(44)(45)(46)(47), areas that have also been linked to a variety of relevant outcomes such as crime and violence (48,49), depression (50), social cognition (51,52), drug use (53,54), and cognitive control (55).…”
Section: Current Practices In Neuroimagingmentioning
confidence: 99%
“…These are areas dominated by low social status, violence, drug dealing, low educational level of parents, unemployment, unsatisfactory health standards, and scanty leisure opportunities. 21 Although some studies have reported an association between neighborhood disadvantage and worse mental health in children and adolescents in developed countries, 22 the consequences of living in poorer neighborhoods for the mental health and QOL of pre-and early adolescents in Brazil have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[23,36] Collective efficacy is a form of cognitive social capital that has been widely used in studies assessing the relationship between neighborhood or community context and health outcomes. Research has documented effects of collective efficacy on a number of health outcomes in children, including adolescent suicidality, [37] asthma, [38] obesity, [39] healthy activities, [40] general health, [41] neglectful and harsh parenting, [42] adolescent sexual risk behavior, [43] and mental health, including antisocial behavior at school entry, [30] internalizing problems among elementary school children, [29] and a composite childhood mental health scale. [44] However, to our knowledge, there are no studies specifically examining the role of collective efficacy on ADHD prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Xue et al found that the prevalence of children with internalizing mental health disorders increased as socioeconomic status in their Chicago neighborhoods decreased. [29] How-ever, this effect was mitigated in neighborhoods with high ratings of collective efficacy and community participation. More recently, Butler et al studied the association between parent-reported neighborhood conditions and childhood internalizing and externalizing mental health conditions, using the same national data set as used in this study, the 2007 NSCH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation